Conserving soils and water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A co-ordinator for Zambia?s Programme Against Malnutrition explains methods of conservation farming which can help to conserve both soil moisture and nutrients in areas experiencing dry spells.